The Role of Therapeutic Drug Monitoring of Anti–Tumor Necrosis Factor Alpha Agents in Children and Adolescents with Inflammatory Bowel Disease. Issue 9 (23rd June 2015) - Joosse, Maria E.; Samsom, Janneke N.; van der Woude, C. Janneke; Escher, Johanna C.; van Gelder, Teun
Abstract : Background: Anti–tumor necrosis factor alpha (TNFα) therapy is effective in pediatric patients with inflammatory bowel disease (IBD) but associated with a risk of developing anti-drug antibodies (ADA) which lower the efficacy. Incorporating measurement of trough levels and ADA (therapeutic drug monitoring) may prevent the development of neutralizing ADA or could contribute to more optimal treatment strategies if ADA are already formed. The aim of this review was to investigate the role of therapeutic drug monitoring in children and adolescents with IBD exposed to anti-TNFα agents. Methods: A literature search identified publications that measured anti-TNFα drug trough levels and/or ADA in children or adolescents with IBD. Studies were eligible when (1) article was written in English, (2) original data were available, (3) full text article or abstract was available, (4) measurement of antibodies against anti-TNFα drugs or trough level of anti-TNFα drugs were reported, and (5) levels were measured in pediatric patients with IBD. Results: The search yielded 811 articles, of which 795 articles were excluded based on title or abstract. A total of 14 studies were included in the review. Conclusions: Therapeutic drug monitoring within the pediatric IBD population certainly has a potential benefit. As occurrence of immune reactions to anti-TNFα agents varies widely, incorporating measurement of IFX trough levels at week 8 or week 14 predicts therapy response and allows for dose adjustments to reach therapeutic drug concentrations. However, a clinically relevant cutoff level for ADA has not been defined yet, and the optimal intervention strategy still has to be determined.